Experience of the Postoperative Intensive Care Treatment of Stanford Type A Aortic Dissection - Lei Bai; Lijuan Ge; Yujing Zhang; Mingliang Li; Bo Jiang; Yanyan Song (International Journal of Clinical Practice)
Objective. To summarize the experience of the postoperative intensive care treatment of Stanford type A aortic dissection (STAAD) following Sun’s procedure. Methods. A total of 124 patients with STAAD who underwent Sun’s procedure from January 2014 to December 2021 at the General Hospital of Ningxia Medical University were retrospectively analyzed. All patients were admitted to the cardiac surgery intensive care unit (ICU) after surgery. According to the perioperative characteristics of the patients with STAAD, intensive care treatment was given to actively prevent the occurrence of postoperative complications. Results. In all the cases enrolled in this study, the causes of aortic dissection comprised hypertension (105 cases), trauma (six cases), Marfan’s syndrome (six cases), and aorto-arteritis (seven cases). The history of past illnesses comprised hypertension (105 cases), coronary disease (25 cases), diabetes mellitus (16 cases), and chronic obstructive pulmonary disease (six cases). There were some preoperative complications, such as cardiac insufficiency, acute liver insufficiency, acute renal insufficiency, pleural effusion, pericardial effusion, pulmonary infection, lower limb ischemia, mesenteric arterial embolism, and digestive tract hemorrhage. The average cardiopulmonary bypass time was 186 ± 32.1 min, the aortic clamp time was 74 ± 12.8 min, the deep hypothermic circulatory arrest time was 21 ± 2.6 min, and the mechanical ventilation time was 34 ± 2.8 h. The average ICU and hospital residence times were 7 ± 1.6 days and 12 ± 3.6 days, respectively. Postoperative complications comprised hypoxemia (34 cases), pulmonary infections (22 cases), tracheostomy (four cases), cerebral hemorrhage (four cases), cerebral infarction (four cases), transient delirium (eight cases), secondary thoracotomies due to bleeding (two cases), alimentary tract hemorrhage (eight cases), and acute renal insufficiency (38 cases). There was no occurrence of hoarseness or chylothorax. There were 15 cases of death, and the total mortality rate was 12.1%. In four cases, the cause of death was one postoperative complication (3.2%), and in 11 cases, the cause of death was multiple postoperative complications (8.9%). The other patients were discharged from the hospital with a good prognosis for full recovery. Conclusion. Postoperative intensive care treatment was an important part of the successful surgical treatment of STAAD.